2021
DOI: 10.3949/ccjm.88a.21010-up
|View full text |Cite
|
Sign up to set email alerts
|

Update to post-acute sequelae of SARS-CoV-2 infection: Caring for the 'long-haulers'

Abstract: The statements and opinions expressed in COVID-19 Curbside Consults are based on experience and the available literature as of the date posted. While we try to regularly update this content, any offered recommendations cannot be substituted for the clinical judgment of clinicians caring for individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…Some studies have shown persistence of at least one symptom in more than half of patients at 110-day follow-up. 3 PASC can even affect young adults who experienced mild symptoms during infection and did not require hospitalization for COVID-19; PASC also can manifest in children, many of whom had asymptomatic COVID-19 infections. 8 Although COVID-19 and PASC are still relatively new phenomena, they have shown similarities to other welldocumented viral respiratory illnesses, such as Middle East respiratory syndrome (MERS) and severe acute respiratory syndrome (SARS), which caused similar postviral disorders including ME/CFS.…”
Section: Learning Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown persistence of at least one symptom in more than half of patients at 110-day follow-up. 3 PASC can even affect young adults who experienced mild symptoms during infection and did not require hospitalization for COVID-19; PASC also can manifest in children, many of whom had asymptomatic COVID-19 infections. 8 Although COVID-19 and PASC are still relatively new phenomena, they have shown similarities to other welldocumented viral respiratory illnesses, such as Middle East respiratory syndrome (MERS) and severe acute respiratory syndrome (SARS), which caused similar postviral disorders including ME/CFS.…”
Section: Learning Objectivesmentioning
confidence: 99%
“…The duration of PASC is unknown and will be defined over time with additional studies. Some studies have shown persistence of at least one symptom in more than half of patients at 110-day follow-up 3. PASC can even affect young adults who experienced mild symptoms during infection and did not require hospitalization for COVID-19; PASC also can manifest in children, many of whom had asymptomatic COVID-19 infections 8.…”
mentioning
confidence: 99%
“…From these studies, it is clear that mindfulness meditation has been associated with a number of healthy inflammatory process changes. 2 Seated meditation has been related to sympathetic nervous system reductions in activation. 48,69,73 The studies that have been reviewed have also found positive meditation on immune cell subsets related to the immune systems.…”
Section: Anti-inflammatory Effects Associated With Meditationmentioning
confidence: 99%
“…From these studies, it is clear that mindfulness meditation has been associated with a number of healthy inflammatory process changes. 2 …”
Section: Anti-inflammatory Effects Associated With Meditationmentioning
confidence: 99%
See 1 more Smart Citation